Managing Organizational Systems As Employee Satisfaction Assessment Standards At Wisatauit Makassar General Hospital - Harniati Harniati; Abdul Rahman; Rismawati Rismawati (Journal of Innovative and Creativity, 2025)
Hospital employee satisfaction can be measured by looking at the organizational management system that is part of every routine activity at the UIT Makassar Tourism Hospital. This source of information can be used among managers to find out the value of organizational management to strengthen supervision and communication efficiency. Employee satisfaction levels can be measured through the Job Description Index (JDI). This study aims to assess the level of employee satisfaction in the organizational management system. The research method used is that the population is all employees at the UIT Makassar Tourism Hospital in 2024 totaling 4345 people with a sample used in this study using the slovin formula of 410 employees. The number of samples in each installation or in each field/section is calculated based on the proportion of the number of employees and the type of employees in each installation or in each field/section. The results of this study stated that most employees were able to make good assessments in each Job Description Index (JDI) indicator, including: General Overview of Job Conditions (78.8%); income and compensation received amounted to (59.0%); the chance of promotion to the position of (67.5%); quality of supervision (74.5%); support for one-unit co-workers is (73.5%) and current working conditions are (72.8%). If the results of the assessment of the six indicators of JDI conclude that the value of employee satisfaction can be stated to be satisfied as seen with the organizational management system at the UIT Tourism Hospital Makassar, therefore there are 12.3% of employees who express dissatisfaction with the organizational management system at the UIT Tourism Hospital in Makassar. The conclusion of the results of this study is that many employees give an assessment that the income and compensation received by employees are bad and very poor. However, this research has implications for increasing income opportunities in the form of salaries as well as opportunities for career paths to be realized through job promotions.